Urgensi Pembelajaran Multiliterasi bagi Mahasiswa Pendidikan Bahasa Indonesia dalam Menghadapi Kurikulum Merdeka - Kemal, Faisal; Haidar, Habiburrohman; Arifin, Imam; Agustine, Elda Yulian (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
The education curriculum in Indonesia has undergone significant changes, with the 2024 launch of the Merdeka Curriculum as the latest innovation. This curriculum demands a more flexible, student-centered learning approach, which requires readiness and adaptive skills from prospective educators, including Indonesian Language Education students. Multiliteracy learning becomes a strategic choice to equip students with the skills needed to face the dynamically changing curriculum. Multiliteracy, encompassing reading, writing, speaking, and digital media usage skills, supports students in comprehending and conveying materials in a profound and engaging manner. In the evolving digital era of the 21st century, multiliteracy skills also equip future educators with critical thinking, collaboration, and problem-solving abilities. This research employs a literature review method to examine the urgency of multiliteracy learning for Indonesian Language Education students. The results indicate that a multiliteracy approach not only enhances students' cognitive skills but also fosters adaptive and innovative attitudes relevant to the Merdeka Curriculum. The urgency of multiliteracy learning is expected to support students in becoming high-quality educators ready to meet the challenges of the new curriculum.